Adamts1 Mediates Ethanol-Induced Alterations in Collagen and Elastin via a FoxO1-Sestrin3-AMPK Signaling Cascade in Myocytes - Hong-Brown, Ly Q. (J Cell Biochem, 2015)
A variety of stressors including alcohol (EtOH) are known to induce collagen production and fibrotic diseases. Matrix metalloproteinases (MMP) play an important role in regulating fibrosis, but little is known regarding the relationship between EtOH and MMPs. In addition, the signaling cascades involved in this process have not been elucidated. We have identified the MMP Adamts1 as a target of EtOH regulation. To characterize the function of Adamts1, we examined EtOH-induced alterations in collagen I and elastin protein levels in C2C12 myocytes. Incubation of myocytes with 100 mM EtOH decreased elastin and increased collagen content, respectively, and these changes were associated with increased O-GLcNAc modification of Adamts1. Conversely, silencing of Adamts1 by siRNA blocked the adverse effects of EtOH on collagen and elastin levels. Similar results were obtained after treatment with a pharmacological inhibitor of MMP. Changes in collagen were due, at least in part, to a decreased interaction of Adamts1 with its endogenous inhibitor TIMP3. The AMPK inhibitor compound C blocked the EtOH-induced stimulation of collagen and O-GLcNAc Adamts1 protein. Changes in AMPK appear linked to FoxO1, since inhibition of FoxO1 blocked the effects of EtOH on AMPK phosphorylation and O-GLcNAc levels. These FoxO-dependent modifications were associated with an upregulation of the FoxO1 transcription target sestrin 3, as well as increased binding of sestrin 3 with AMPK. Collectively, these data indicate that EtOH regulates the collagen I and elastin content in an Adamts1-dependent manner in myocytes. Furthermore, Adamts1 appears to be controlled by the FoxO1-sestrin 3-AMPK signaling cascade.